DIPLOMASI TIONGKOK TERHADAP AMERIKA SERIKAT DALAM PARIS AGREEMENT TAHUN 2015-2016 - Komeini, Ayatullah; Rani, Faisyal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research describes the China‟s diplomacy in a global climate change agreement. This research will focus on how China‟s diplomacy in paris climate change agreement towards the United States. This study interesting because describe about the diplomatic efforts of China as developing country and the world‟s biggest emitter of carbon dioxcide towards United States as developed country in global agreement on climate change.Climate change is recognized as a threat to international peace and security. The Paris Agreement marks a global commitment to tackling climate change and to reduction greenhouse gas in the world. I argue that diplomacy plays a significant role in process of climate treaty making. China's diplomacy as a developing countries toward the United States in the paris agreement has affected the United States policy in global climate agreement from convenient country towards commited country.China‟s Diplomacy in paris agreement has resulted ratification of the United States through joint ratification in China. For the first time, an international agreement to reduce greenhouse gas emissions includes contributions from all of the major emitting countries and, indeed, a large majority of the countries of the world.Keywords: Diplomacy, China, United States, Global Climate Change, Paris Agreement